Cross–layer–based reliable robust transmission for emergency messages in high mobility unreliable VANET networks. (24th March 2015) - Chang, Ben–Jye; Liang, Ying–Hsin; Yang, Tsung–Yuan
To achieve active safe driving has become a key trend in intelligent transport systems (ITS). However, in the high–mobility unreliable vehicular ad–hoc networks (VANETs), the emergency messages or the driving videos are difficult to be sent to the receivers, the platoon leader or the cloud server in time. The reliable end–to–end transmission protocol suffers from extremely unreliable links, high mobility, and hardly providing an accurate congestion window (cwnd) for transmissions. This paper proposes a Cross–Layer–based reliable robust CL–TCP to forward real–time emergency messages. CL–TCP proposes several TCP states: congestion, loss, unstable, frozen and disconnecting, to control TCP cwnd according to the status of L2 and L3 protocols. The Enhanced AODV (EAODV) algorithm is proposed to increase path reliability and maximize throughput. The designed cross–layer messages include: CL_EAODV, CL_ICMP_FB, CL_ICMP_DU, etc. Numerical results demonstrate CL–TCP outperforms others in goodput, number of link–breaks, average packet delivery ratio. Furthermore, CL–TCP yields a higher fairness among TCP connections.